ANALISIS EFEKTIVITAS PENERAPAN SISTEM PENGENDALIAN INTERNAL (STUDI PADA KANTOR JAMINAN MUTU UGM) - , ANDI TENRIPAKKUA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of this study was to analyze the implementation effectiveness of internal control system (ICS) in quality assurance office of Gadjah Mada University. A critical qualitative approach was used in this study to describe, represent and assess condition